KEEFEKTIFAN MODEL PICTURE AND PICTURE BERBANTU MEDIA GASER TERHADAP KEMAMPUAN MENULIS KARANGAN NARASI KELAS V SD NEGERI KARANGREJO 2 BONANG SEMESTER GENAP TP 2018/2019 - Munna, Ika Shofwatul; Purwadi, Purwadi; Mudzanatun, Mudzanatun (JGK (Jurnal Guru Kita), 2019)
Abstract: The Effectiveness Of The Picture And Picture Models Assisting Gaser Media Towards Writing Ability Narration In Class V Subject SD N Karangrejo 2 Bonang Even Semester TP 2018/2019. The purpose of this study was to determine the effectiveness of the picture and picture model assisted by gaser media on the ability to write narrative essays of  grade V students SD N Karangrejo 2 Bonang. The research method used is quantitative research. The research instrument used was an interview sheet, a question instrument in the form of description, and documentation of student learning outcomes. The collection techniques used in this study were interviews, tests, and documentation. The results of the study using t-test two samples obtained t count = -2.29157> t table = 2.01537. Because tcount> t table, then H0 is rejected which means that the narrative essay writing skills of students in the experimental class are different from the control class. It can be concluded that the Picture And Picture model is assisted by effective media on the ability to write narrative essays in V grade students SD N Karangrejo 2 Bonang Even Semester 2018/2019. The t test for one sample obtained t = 3,632932> t table = 2,06866. Because tcount> t table. Then H0 is rejected, so it can be concluded that students' narrative writing skills can achieve good criteria by applying the Picture And Picture learning model to media images.Keywords: Picture And Picture, cheerful, writing narrative essaysAbstrak: Keefektifan Model Picture And Picture Berbantu Media Gaser Terhadap Kemampuan Menulis Karangan Narasi Kelas V SD Negeri Karangrejo 2 Bonang Semester Genap TP 2018/2019. Tujuan penelitian ini adalah untuk mengetahui keefektifan model picture and picture berbantu media gaser terhadap kemampuan menulis karangan narasi siswa kelas V SD N Karangrejo 2 Bonang.Metode penelitian yang digunakan adalah penelitian kuantitatif.Instrumen penelitian yang digunakan adalah lembar wawancara, instrumen soal bentuk uraian, dan dokumentasi hasil belajar siswa.Teknik pengumpulan data yang digunakan penelitian ini adalah wawancara, tes, dan dokumentasi. Hasil penelitian menggunakan uji t dua sampel diperoleh thitung = -2,29157>ttabel = 2,01537. Karena thitung > ttabel, maka H0 ditolak yang berarti keterampilan menulis karangan narasi siswa pada kelas eksperimen berbeda dari kelas kontrol. Dapat disimpulkan bahwa model Picture And Picture berbantu media gaser efektif terhadap kemampuan menulis karangan narasi siswa kelas V SD N Karangrejo 2 Bonang Semester Genap 2018/2019.  Uji t satu sampel diperoleh thitung=3,632932>ttabel=2,06866. Karena thitung > ttabel. Maka H0 ditolak, sehingga dapat disimpulkan bahwa keterampilan menulis narasi siswa dapat mencapai kriteria baik dengan penerapan model pembelajaran Picture And Picture berbantu media gambar seri.Kata Kunci : Picture And Picture, gaser, menulis karangan narasi